The demise of sovereign wealth funds - Di Bonaventura Altuve, L (Taylor & Francis, 2023)
Sovereign wealth funds (SWFs) embody the state’s growing insertion in the global financial system. While the bulk of the SWF literature has centred around the dynamics behind their establishment and geopolitical utility, there is very little research on the factors behind SWF exhaustion. Drawing from conventional political and economic explanations, this article finds that SWFs are almost always depleted in highly unstable political environments, while economic crises rarely impact SWFs to the point of exhaustion. The article presents a theoretical foundation for SWF exhaustions by examining political instability in different regime types. In weakly institutionalized regimes, SWFs are more prone to exhaustion as incumbents govern in recurrently uncertain environments and prioritize short-term goals, which are typically incompatible with funds’ objectives. Conversely, highly institutionalized regimes enjoy greater stability and certainty, which sustain the long-term nature of SWFs. The argument is substantiated through a comparative analysis contrasting the effects of (in)stability in Venezuela’s exhausted FIEM and FONDEN and Azerbaijan’s resilient SOFAZ.